Section 10 of the Artemis Accords (on the natural resources of space, the moon and other celestial bodies) - Gutiérrez Espada, Cesáreo (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The Artemis Accords promoted by the United States were signed in 2020 by a group of States that has grown to reach (with Greece in 2024) the number of 34. One of its most relevant issues refers to the issue of the exploitation of the natural resources of space itself and of the Moon and other celestial bodies. In this matter, the ultimate objective of the Agreements is to achieve the legality of the extraction of the Moon’s natural resources.The success of these texts among States leads us to think that if not in the near future, the principle of legality of extracting natural resources from space could be a reality.The thesis of this work defends the convenience of the issue being assessed and resolved within the United Nations bodies on Space Law. And, also, that the final result of this effort safeguards the interest of all Humanity in the enjoyment of the benefits that can be obtained from the natural resources of space.
Keywords: Interpretación of treaties; international treaty; non-appropriation principle; polítical texts; “rare earth elements” (RRE); safe zones